Human Tissues Act, 1974: The Present And The Future - Syed Ismail, Shamsiah Begum (Journal of Malaysian and Comparative Law, 2019)
The main part of this paper is in respect of the Human Tissues Act, 1974 which governs the Malaysian law relating to procurement of cadaveric organs for various purposes, including transplantation. I shall begin by considering briefly the various procurement policies concerning cadaveric organs and the principles that underpin human organs transplant schemes generally, before proceeding to the Act. The discussion that is to follow will be based on two assumptions, which might be controversial themselves, that there is a need to increase the supply of organs in order to save lives and/or enhance the quality of those lives, and that societal efforts to increase the supply of organs should remain with certain ethical boundaries.